The Effect of Problem Based Learning Model on Understanding Concepts and Problem Solving Skill in Social Sciences in Grade IV Students of SDN 1 Mulung Driyorejo Gresik - Muliyono, Miftaqul Rizqi; Suyanto, Totok; Yani, Muhammad Turhan (International Journal for Educational and Vocational Studies, 2019)
This study aims to determine whether the use of the problem-based learning model can influence the understanding of concepts and problem-solving skills in social studies learning in the fourth grade of SDN 1 Mulung. This study uses a quantitative method with quasi-experimental design type nonequivalent sampled group design. The dependent variable in this study is the understanding of concepts and problem-solving skills, and the different variables are problem-based learning models. The sample chosen in this study uses namely IV-A class students totaling 20 students and IV-B class students totaling 20 students, using the sample random sampling technique. Data collection techniques using tests (pre-test and post-test). The research instrument used was a test sheet for understanding concepts and problem-solving skills. Instrument analysis technique uses validity test and reliability test while the data analysis technique uses the normality test, homogeneity test, hypothesis test, and normalized n-gain test. Based on the calculation of the T-test, Sig. (2-tailed) That is equal to 0,000 <0,05, then Ha is accepted, or there are significant differences between the difference between the results of the post-test and pre-test of the control class with the difference between the results of the post-test and the pre-test of the experimental class. This can be interpreted that the problem-based learning model has a significant effect on the understanding of concepts and problem-solving skills in social studies learning in the fourth grade of SDN 1 Mulung on natural resource material. To provide effective, interesting, and fun learning for students, teachers, should use an interesting learning model.